Fractography of Fatigue Fracture Surface in Silumin Subjected to Electron-Beam Processing; IOP Conference Series: Materials Science and Engineering; Vol. 142 : Innovative Technologies in Engineering - Konovalov S. V.; Aksenova K. V.; Gromov V. E.; Ivanov Yu. F. Yuriy Fedorovich; Semina O. A. (2016, 2016)
Title screen